1983
DOI: 10.1002/aja.1001680405
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiology of the intestinal tract of the mouse

Abstract: This paper summarizes recent and continuing work on circadian rhythms in the alimentary tract of rodents; these include: (1) cell proliferation, (2) activities of intestinal enzymes, and (3) behavioral aspects of spontaneous feeding and drinking. All regions of the intestinal tract show marked circadian behavior in cell proliferation. The roles of the light-dark cycle and meal timing in synchronizing such rhythms are discussed as well as the influence of epidermal growth factor, insulin, glucagon, and ACTH 1-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 73 publications
2
30
0
Order By: Relevance
“…The higher FE caused by feeding in the morning may be attributed to low-maintenance requirements, efficient nutrient accumulation or an alteration in body composition. Circadian rhythms of cell proliferation, intestinal enzymes, monosaccharide transport, and the height and width of villi in the intestinal tract are entrained (or synchronized) to the feeding schedule; however, numerous enzyme rhythms persist in fasting animals (Scheving et al, 1983). Pigs that were fed identical meals at 12-h intervals showed higher amino-acid utilization and lower plasma urea response in the morning than in the evening (Koopmans et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The higher FE caused by feeding in the morning may be attributed to low-maintenance requirements, efficient nutrient accumulation or an alteration in body composition. Circadian rhythms of cell proliferation, intestinal enzymes, monosaccharide transport, and the height and width of villi in the intestinal tract are entrained (or synchronized) to the feeding schedule; however, numerous enzyme rhythms persist in fasting animals (Scheving et al, 1983). Pigs that were fed identical meals at 12-h intervals showed higher amino-acid utilization and lower plasma urea response in the morning than in the evening (Koopmans et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cell mitosis occurs at a specific time of day in animal tissues in vivo (2)(3)(4)(47)(48)(49), suggesting that the timing of cell mitosis is gated by the circadian cycle. Therefore, we hypothesized that there would be a consistent phase relationship between the circadian and cellcycle rhythms in cultured cells.…”
Section: Resultsmentioning
confidence: 99%
“…There are substantial evidences that progression through the cell cycle occurs at specific times of the day/night cycle, suggesting that a function of the circadian clock system is to control this fundamental process. 42,[48][49][50] Indeed, microarray analyses revealed that key elements of the cell cycle machinery including cyclin D1, cyclin B1, cyclin E, cyclin A, P53, Wee1, c-myc, Mdm2 and Gadd45 exhibit circadian-dependent expression (Table 2). 51 …”
Section: Clock-related Genes Regulate the Transcription Of Cell Cyclementioning
confidence: 99%